Hubungan Pengetahuan, Sikap Dan Perilaku Ibu Tentang Perawatan Perineum Terhadap Lama Penyembuhan Luka Jahitan Perineum di Wilayah Kerja UPTD Puskesmas Campaka Cianjur Tahun 2023 - Tupah Tupah; Maryam Syarah M; Istiana Kusumastuti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Perineal wounds are injuries to the urogenital diaphragm and anal muscle during vaginal delivery, either normal delivery or instrumental delivery. Knowledge is a very important domain for the formation of a person's attitudes and behavior. The aim of the research was to determine the relationship between maternal knowledge, attitudes and behavior regarding perineal suture wound care and the healing time for perineal suture wounds. This type of quantitative research with a cross sectional design. The research was conducted in June-July 2023. The research population was postpartum mothers with perineal wounds in June-July 2023. The total was 30 people. The population in this study was 30 people. The sampling technique is the total sampling population. The research results obtained from 30 respondents showed that there were 22 mothers who had good knowledge (73.3%), 22 mothers who had a positive attitude (73.3%), 23 mothers who had good behavior (76%). .7%). The results of the Chi-Square analysis test for the knowledge category obtained a p value = 0.002 (p = <0.05), for the attitude category the p value = 0.002 < (0.05) while for behavior the p value = 0.001 < (0). .05). The conclusion is that there is a relationship between knowledge, attitudes and behavior regarding perineal wound care and the healing time for perineal wound sutures in the work area of the UPTD Campaka Community Health Center in 2023. The suggestion is that postpartum mothers should improve their behavior regarding wound care as an effort to speed up the healing of perineal wounds.